Heteroleptic Germanium(II) and Tin(II) chlorides supported by anionic ligands derived from 2,3-dimethyl-1,4-diaza-1,3-butadiene - Chia, Siew-Peng (2014)
The syntheses and structures of heteroleptic germanium(II) and tin(II) chlorides supported by anionic ligands derived from 2,3-dimethyl-1,4-diaza-1,3-butadiene are described. The reaction of ArN=C(Me)C(Me)=NAr (L, Ar = 2,6-iPr2C6H3) with MeLi in Et2O, followed by treatment with GeCl2·dioxane or SnCl2, afforded [L1ECl] [L1 = ArN=C(Me)C(Me)2NAr; E = Ge (1), Sn (2)]. Moreover, L2Li [L2 = ArN=C(Me)C(=CH2)NAr] reacted with GeCl2·dioxane in Et2O to form [{C(=CH)NAr}{C(Me)=NAr}]2(GeCl)2 (3). The byproducts are [{C(CH2)NAr}{C(Me)=NAr}Ge]2 (4) and L2H (5). Furthermore, the reaction of L with LiNiPr2 in Et2O, followed by treatment with SnCl2, afforded [L2SnCl] (6). Compounds 1–4 and 6 have been characterized by NMR spectroscopy and X-ray crystallography.